Performance Analysis of Signalized Intersections (Case Study: Kragan Street-Veteran Street Gresik) - Kholidia Ayunaning; Ridho Maulana Hakim (Journal of Development Research, 2023)
The signalized intersection of Kragan Street-Veteran Street Gresik is the gateway to and from Gresik Regency and Surabaya City, so there are often traffic jams or delays at this signalized intersection and accidents. The evaluation of the performance of the signalized intersection of Kragan Street-Veteran Street Gresik shows that the signalized intersection Kragan Street-Veteran Street is experiencing saturation obtained from the 1994 MKJI signalized intersection performance analysis method. According to the Ministry of Transportation regulation No. 96 of 2015, the signalized intersection of Kragan Street – Veteran Street is included in the category D level in signaled crossing services.